2023
DOI: 10.3390/antib12030049
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms in Acute and Persisting Forms of COVID-19 Associated with Neural Autoantibodies

Abstract: (1) Background: In this narrative review, we focus on neural autoantibodies in patients with coronavirus disease 2019 (COVID-19) as a consequence of severe acute respiratory syndrome coronavirus type 2 infection and persisting symptoms of post-COVID-19 syndrome with a psychiatric presentation. (2) Methods: Our methods include using the PubMed database to search for appropriate articles. (3) Results: We first describe the phenomenon of the psychiatric manifestation of COVID-19 in acute and persistent forms, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Антитела к интерферону Тяжесть COVID-19 [121][122][123] Антитела к хемокинам (СXCL17, CCL18, CCL22) Протективный эффект [186] Антитела к ИЛ-1Ра Нарушение иммунорегуляции [187] Антитела к сурфактанту легких Нарушение функции легких [185] Антинейрональные антитела (ARHGAP31, GAD65, рецепторы ацетилхолина, В1.2б MOG, NMDA, MCTP1, Yo, миелин, Ma/Ta2) Невропсихиатрические проявления COVID-19 [305] Антитела к рецепторам вазорегуляции и вегетативной нервной системы Неврологические нарушения при длительном COVID [306] Антитела к ТФ4-комплексу гепарин -ТФ4 Тяжесть COVID-19 [152], тромботическая тромбоцитопения после вакцинации против SARS-CoV-2 [153] Примечание: NETs -«нейтрофильные внеклеточные ловушки» (neutrophil extracellular traps) Научно-практическая ревматология. 2024;62(1):32-54…”
Section: антинуклеарные антителаunclassified
“…Антитела к интерферону Тяжесть COVID-19 [121][122][123] Антитела к хемокинам (СXCL17, CCL18, CCL22) Протективный эффект [186] Антитела к ИЛ-1Ра Нарушение иммунорегуляции [187] Антитела к сурфактанту легких Нарушение функции легких [185] Антинейрональные антитела (ARHGAP31, GAD65, рецепторы ацетилхолина, В1.2б MOG, NMDA, MCTP1, Yo, миелин, Ma/Ta2) Невропсихиатрические проявления COVID-19 [305] Антитела к рецепторам вазорегуляции и вегетативной нервной системы Неврологические нарушения при длительном COVID [306] Антитела к ТФ4-комплексу гепарин -ТФ4 Тяжесть COVID-19 [152], тромботическая тромбоцитопения после вакцинации против SARS-CoV-2 [153] Примечание: NETs -«нейтрофильные внеклеточные ловушки» (neutrophil extracellular traps) Научно-практическая ревматология. 2024;62(1):32-54…”
Section: антинуклеарные антителаunclassified
“…Encephalopathy and encephalitis associated with COVID-19 and PASC are often mediated by the production of neural autoantibodies. These conditions may subsequently lead to various neuropsychiatric symptoms [24]. Franke et al [25] found neuronal autoantibodies in more than 50% of COVID-19 survivors with persistent cognitive impairment.…”
Section: Pathophysiological Backgroundmentioning
confidence: 99%